Development of “Egg Countcrate Box” Media Oriented to Ausubel’s Learning Theory on Addition and Subtraction Material for 1st Grade Elementary School - Wuriani, Eka Indah; Nuraini, Ni Luh Sakinah; Yuniawatika, Yuniawatika (Proceedings Series of Educational Studies, 2024)
Mathematics in elementary school presents basic concepts that are useful for higher levels of education, including addition and subtraction. This material is taught starting from simple operations to more complex levels. Difficulty understanding basic concepts can hinder students' ability to absorb more advanced material. Therefore, to help students overcome their understanding problems, effective learning media is needed. Following Ausubel's learning theory, this research aims to develop Egg Countcrate Box media that is valid, practical and effective. Students will have a more interesting learning experience and develop a stronger desire to learn with the help of this medium. This research supports the importance of relevant learning according to Ausubel's learning theory, where this kind of learning helps students absorb and remember new material by relating it to what they already know. The RnD process in this research follows the ADDIE framework. The research results show that the media expert validation test has an average value of 97% and the material expert validation test has an average value of 91%. Experts provided several comments and provided minor revisions, but the Egg Countcrate Box media is still very valid for use. The teacher's assessment received an average score of 98% and students 99.5% based on data from small-scale and large-scale trials. Thus, this media practicality category is very practical without revision. There was an average increase of 0.67 in the media effectiveness test calculated using N-Gain analysis. The results from the N-Gain category are in the quite effective range, namely between 0.56-0.75. The results of testing the Egg Countcrate Box media for validity, practicality and effectiveness show that this media is very valid, very practical and effective enough to be the right choice for teaching basic counting skills. Keywords: egg countcrate box; ausubel; addition and subtraction